Investigação de infecção por Chlamydophila pneumoniae em crianças asmáticas por Microimunofluorescência e Elisa - Jairo Fernandes dos Reis Junior (2009)
Asthma is a chronic inflammatory disorder of the airways associated with environmental factors, genetic, immunological, occupational, infectious, among others, which may contribute to the onset of disease, and for exacerbation of their symptoms. Respiratory infections play an important role in promoting tissue damage observed in asthma. Chlamydophila pneumoniae is an obligate intracellular bacterium associated with respiratory tract infections. Transmitted person - to person contact through respiratory secretions has been associated withseveral chronic respiratory conditions, including asthma. In this work we evaluated the frequency of specific anti - C. pneumoniae between asthmatics and non asthmatics and compared the performance of two serological tests used in diagnosis of infection: microimmunofluorescence (MIF) and ELISA. We also investigate an association between the presence of bacteria and asthma in sixtyvolunteers between 4 and 15 years old, 30 asthmatic and 30 non-asthmatics. 8.3%, 5 % and 10% among asthmatic patients were positive for IgA, IgG and IgM respectively. 3.4 %, 10 % and 1.7 % were positive for these antibodies among nonasthmatics. In the ELISA test, 11.7% were positive for IgG (p> 0.05). 5 % were positive for IgM, all male and belonging to the group of asthmatics (p = 0.2373). There was agreement in the results of the two methods was 93.3 % and to 88.3 %for IgG and IgM, respectively. Sensitivity, specificity, negative predictive value and positive ELISA test for the detection of IgG compared with MIF were 66.7, 98, 94.3 and 85.7 %, respectively. Similarly, the results for IgM were 50, 98, 96.2 and 66.7 %, respectively. There was a higher prevalence of antibodies among young people aged over 10 years (p = 0.0729). Statistically significant difference (p = 0.0287) was observed between asthmatic subjects using corticosteroids and those who didnot use medication. Serological evidence of the presence of infection by the bacteria was higher among those taking the drug, indicating that these drugs may predispose patients to infection. The use of two methods to detect anti - C.pneumoniae has shown that patients on corticosteroids are more susceptible to this infection in this population; however MIF was more appropriate for this purpose. It is necessary to continue the study with a larger number of patients for 19 more accurate assessment of the association between asthma and Chlamydophilapneumoniae.